Testing the REBT-I model in athletes: Investigating the role of self-confidence between irrational beliefs and psychological distress. (November 2022) - Mansell, Paul C.; Turner, Martin J.
Abstract: Evidence suggests that, in the general population, instances of poor mental health have increased over recent years and are set to continue to grow. Athletes may experience a plethora of additional stressors, such as injury, de-selection, and competitive anxiety. Prior research has suggested that irrational beliefs may maladaptively influence an athlete's wellbeing, but little is known about the role of self-confidence in these relationships. The present study aimed to examine the role which self-confidence plays as part of the REBT-I model in athletes. Broadly speaking, it was hypothesised that primary irrational beliefs would relate negatively to self-confidence through secondary irrational beliefs. In turn, self-confidence was hypothesised to relate negatively to competitive anxiety and depressive symptoms. Additionally, irrational beliefs were hypothesised to combine with low self-confidence to relate negatively to competitive anxiety and depressive symptoms. Four hundred and ten athletes ( n  = 227 females, M age = 33.91 years, SD  = 14.84) completed an online questionnaire pack assessing irrational beliefs, self-confidence, cognitive and somatic competitive anxiety, and depressive symptoms. Using path analysis, the tested hypothesised model demonstrated an excellent fit to the data. Findings demonstrate some support for the REBT-I model in that primary irrational beliefs predict competitive anxiety and depressive symptoms through secondary irrational beliefs. Results extend the REBT-I model by including self-confidence as a mediating factor between depreciation beliefs and competitive anxiety and depressive symptoms. Findings suggest practitioners should be aware of the role that irrational beliefs may have in negatively influencing self-confidence and subsequent depression symptomology in athletes. Highlights: Some support for the REBT-I model was found. Demandingness related to self-confidence, competitive anxiety, and depressive symptoms through secondary irrational beliefs. Self-confidence related to competitive anxiety and depressive symptoms. Practitioners may target depreciation beliefs to enhance self-confidence and wellbeing.